Egg-shaped core/shell α-Mn2O3@α-MnO2 as heterogeneous catalysts for decomposition of phenolics in aqueous solutions - Saputra, E.; Zhang, H.; Liu, Q.; Sun, Hongqi; Wang, S. (Elsevier, 2016)
Novel uniform ellipsoid a-Mn2O3@a-MnO2 core/shell (McMs) nanocomposites were prepared via a hydrothermal process with a shape-control protocol followed by calcination at different temperatures. The properties of the composites were characterized by a number of techniques such as thermogravimetric analysis (TGA), X-ray diffraction (XRD), N2 adsorption, and scanning electron microscopy (SEM). The core/shell materials were much effective in heterogeneous oxone® activation to generate sulfate and hydroxyl radicals for degradation of aqueous phenol. The McMs composites demonstrated catalytic activity for 100% phenol decomposition in short duration varying between 20 and 120 min, much higher than that of homogeneous Mn2+ system with 95% phenol degradation in 120 min. They also showed a higher activity than single-phase a-Mn2O3 or a-MnO2. The catalytic activity of phenol degradation depends on temperature, oxone® concentration, phenol concentration, and catalyst loading. The catalysts also showed a stable activity in several cycles. Kinetic study demonstrated that phenol degradation reactions follow a first order reaction on McMs catalysts giving activation energies at 32.1–68.8 kJ/mol. With the detection of radicals by electron paramagnetic resonance (EPR), the generation mechanism was proposed.